Masculine attitudes of superiority deter men from accessing antiretroviral therapy in Dar es Salaam, Tanzania - Tumaini M. Nyamhanga; Eustace P.Y. Muhondwa; Rose Shayo (Taylor & Francis Group, 2013)
Background: This article presents part of the findings from a larger study that sought to assess the role that gender relations play in influencing equity regarding access and adherence to antiretroviral therapy (ART). Review of the literature has indicated that, in Southern and Eastern Africa, fewer men than women have been accessing ART, and the former start using ART late, after HIV has already been allowed to advance. The main causes for this gender gap have not yet been fully explained. Objective: To explore how masculinity norms limit men's access to ART in Dar es Salaam. Design: This article is based on a qualitative study that involved the use of focus group discussions (FGDs). The study employed a stratified purposive sampling technique to recruit respondents. The study also employed a thematic analysis approach. Results: Overall, the study's findings revealed that men's hesitation to visit the care and treatment clinics signifies the superiority norm of masculinity that requires men to avoid displaying weakness. Since men are the heads of families and have higher social status, they reported feeling embarrassed at having to visit the care and treatment clinics. Specifically, male respondents indicated that going to a care and treatment clinic may raise suspicion about their status of living with HIV, which in turn may compromise their leadership position and cause family instability. Because of this tendency towards ‘hiding’, the few men who register at the public care and treatment clinics do so late, when HIV-related signs and symptoms are already far advanced. Conclusion: This study suggests that the superiority norm of masculinity affects men's access to ART. Societal expectations of a ‘real man’ to be fearless, resilient, and emotionally stable are in direct conflict with expectations of the treatment programme that one has to demonstrate health-promoting behaviour, such as promptness in attending the care and treatment clinic, agreeing to take HIV tests, and disclosing one's status of living with HIV to at least one's spouse or partner. Hence, there is a need for HIV control agencies to design community-based programmes that will stimulate dialogue on the deconstruction of masculinity notions.